Performance Comparison of Widely-Used Maximum Power Point Tracker Algorithms under Real Environmental Conditions - Durusu, Ali; Nakir, Ismail; Ajder, Ali; Ayaz, Ramazan; Akca, Hakan; Tanrioven, Mugdesem (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2014)
Maximum power point trackers (MPPTs) play an essential role in extracting power from photovoltaic (PV) panels as they make the solar panels to operate at the maximum power point (MPP) whatever the changes of environmental conditions are. For this reason, they take an important place in the increase of PV system efficiency. MPPTs are driven by MPPT algorithms and a number of MPPT algorithms are proposed in the literature. The comparison of the MPPT algorithms in literature are made by a sun simulator based test system under laboratory conditions for short durations. However, in this study, the performances of four most commonly used MPPT algorithms are compared under real environmental conditions for longer periods. A dual identical experimental setup is designed to make a comparison between two the considered MPPT algorithms as synchronized. As a result of this study, the ranking among these algorithms are presented and the results show that Incremental Conductance (IC) algorithm gives the best performance.
Keywords: Maximum power point trackers; outdoor conditions; performance evaluation; photovoltaic system; OPTIMIZATION; Computer Science; Engineering